Antarctic Phytoplankton Assemblages in the Marginal Ice Zone of the Northwestern Weddell Sea - Kang, Sung-Ho; Kang, Jae-Shin; Lee, Sanghoon; Chung, Kyung Ho; Kim, Dongseon; Park, Myung Gil (Journal of Plankton Research, 2001)
The waters around the northern tip of the Antarctic Peninsula show complex patterns of water circulation due to mixing of diverse water masses. Physicochemical properties of the different water types should affect the distribution, biomass and species composition of the phytoplankton assemblages. We examined these features in the marginal ice zone (MIZ) of the northwestern Weddell Sea. Areas with the higher biomass were located in the Weddell Sea MIZ where the surface waters were relatively stable due to the sea-ice melting. In these waters, the colonial stage of Phaeocystis antarctica and micro-sized chain-forming diatoms accounted for 70% of the total phytoplankton carbon. Waters in the Bransfield Strait region, in contrast, were characterized by a dominance of nanoflagellates, which accounted for 80% of the total phytoplankton carbon. Our observations support the hypothesis that the species composition of phytoplankton communities is a function of the different water mass, reflecting the physical conditions of the upper water column, particularly its stability.